2003
DOI: 10.1063/1.1628388
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of electromigration-induced failure in the 97Pb–3Sn and 37Pb–63Sn composite solder joints

Abstract: The electromigration-induced failure in the composite solder joints consisting of 97Pb–3Sn on the chip side and 37Pb–63Sn on the substrate side was studied. The under-bump metallization (UBM) on the chip side was 5 μm thick electroplated Cu coated on sputtered TiW/Cu and on the substrate side was electroless Ni/Au. It was observed that failure occurred in joints in a downward electron flow (from chip to substrate), while those joints having the opposite current polarity showed only minor changes. During electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(67 citation statements)
references
References 11 publications
0
67
0
Order By: Relevance
“…2 However, the interface between the scallops and Cu has been investigated, except that it was assumed that the interfacial diffusion of Cu is fast and the diffusion is not a rate limiting step. In spite of the very large body of literature published on the subject of solder/Cu reaction, [3][4][5][6][7][8][9][10][11][12] the structural informa-tion of the interface and the crystallographic orientation reaPresent address: Jet Propulsion Laboratory, Pasadena, California; electronic mail: Jong-ook.Suh@jpl.nasa.gov lationship between the IMC and Cu is still missing. It is the purpose of this study to determine the orientation relationship and the statistical distribution experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, the interface between the scallops and Cu has been investigated, except that it was assumed that the interfacial diffusion of Cu is fast and the diffusion is not a rate limiting step. In spite of the very large body of literature published on the subject of solder/Cu reaction, [3][4][5][6][7][8][9][10][11][12] the structural informa-tion of the interface and the crystallographic orientation reaPresent address: Jet Propulsion Laboratory, Pasadena, California; electronic mail: Jong-ook.Suh@jpl.nasa.gov lationship between the IMC and Cu is still missing. It is the purpose of this study to determine the orientation relationship and the statistical distribution experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in-situ observation of the microstructural variation during the current stressing of the solder joints should be conducted to evaluate the effects of the two factors. The primary cause for current crowding is reported 15,16) to be the line-to-bump geometry of the solder bump joint, resulting in a higher current density in the solder regime than the average current density. However, the primary contributor for Joule heating in the solder joints is reported 15,16) to be the extremely thin and small dimension of Cu or Al traces on the Si chip.…”
Section: )mentioning
confidence: 99%
“…5) Previous reports have indicated that the evolution of microstructural features and mechanical properties of solder alloys were significantly related to the EM effect by applying the DC power. [6][7][8] In general, solders stressed with current density above 10 8 AÁm À2 for several hours will trigger the EM effect, 9,10) and so will solders with a lower level of current density. 5,11,12) However, the EM effect can be ignored in the case of alternating current (AC) power.…”
Section: Introductionmentioning
confidence: 99%